First insight on the genesis of iron oxide-hydroxide biospeleothems in Rancho Chico Lava Tube, Mexico - López-Martínez, Rafael; Solleiro-Rebolledo, Elizabeth; Alcántara-Hernández, Rocio; Pi Puig, Teresa; Sedov, Sergey; Valera Fernández, Daisy; Luis-Vargas, M. Nayeli; Lima Vera, Yasmany; Solé, Jesús; Espinasa-Pereña, Ramon (International journal of speleology, 2025)
Iron is a common element in lava tube systems, typically observed as thin crusts or inferred from the reddish coloration of secondary mineral deposits. In this study, we describe iron oxide-hydroxide biospeleothems discovered in the Rancho Chico Lava Tube, located within the Xalapa Monogenetic Volcanic Field in Mexico. We adopt an integrative approach combining petrography, soil micromorphology, scanning electron microscopy, mineralogy, and 16S rRNA gene metabarcoding. DNA sequencing reveals the presence of microorganisms such as Acidithiobacillus , Gallionella , and members of the Leptospirillaceae family, which may be involved in the oxidation of Fe²⁺ within the lava tube. The source of iron appears to originate from the overlying soil, where pedogenic processes, including oxidation-reduction reactions, facilitate its mobilization.